Factors Associated with the Implementation of Medical Records at the Konawe District Health Center, Indonesia - ulva, sitti marya; Nurleni, Nurleni; Saafi, La Ode; Sunarsih, Sunarsih; Jayadipraja, Erwin Azizi; Bahtiar, La Ode (YCAB Publisher, 2025)
Background:The implementation of medical records is vital to ensuring quality healthcare services by supporting patient care, administrative functions, and policy development. However, challenges such as limited resources, inadequate training, and insufficient infrastructure often hinder optimal medical record practices in health centers, particularly in developing regions like Konawe District, Indonesia. Objective:This study aims to analyze the factors related to the implementation of medical records at the Konawe District Health Center. Methods:A quantitative case-control study design was employed. The study population included all officers responsible for service quality at the health center, such as the head of the health center, administrative staff, and the person in charge of medical records. A total of 124 respondents were selected using the Simple Random Sampling technique. Results:The findings indicated significant relationships between various factors and the implementation of medical records: adequate funding positively impacted medical record practices; skilled and trained personnel improved medical record implementation; Effective time management and adaptability supported better practices; strong leadership and organizational support enhanced medical record processes; adequate infrastructure was crucial for successful medical record management. Conclusion:The study concludes that financial, human resource, organizational, time of change, and infrastructural factors significantly influence the implementation of medical records at the Konawe District Health Center. Addressing these factors is essential to improving medical record practices and overall healthcare service quality. Keywords:finance; human resources; time of change; organization; infrastructure; medical records